A novel SLC12A1 mutation in Bedouin kindred with antenatal Bartter syndrome type I. (12th April 2019) - Halperin, Daniel; Dolgin, Vadim; Geylis, Michael; Drabkin, Max; Yogev, Yuval; Wormser, Ohad; Schreiber, Ruth; Shalev, Hanna; Landau, Daniel; Birk, Ohad S.
Abstract: Four affected individuals of consanguineous kindred presented at infancy with an apparently autosomal recessive syndrome of polyuria and hypokalemic metabolic alkalosis, following maternal polyhydramnios and premature delivery, culminating in severe failure to thrive. Hypercalciuria, nephrocalcinosis, and hyperaldosteronism were further apparent as well as an unusual finding of intermittent hypernatremia. Additionally, all patients demonstrated variable micrognathia with upper respiratory airway abnormalities. As neither postnatal hyperkalemia nor permanent hearing deficits were shown, clinical assessment was consistent with antenatal Bartter syndrome (ABS) type I, which was never described before in the Israeli Bedouin population. Through genome‐wide linkage analysis, we identified a single ∼3.3 Mbp disease‐associated locus on chromosome 15q21.1, segregating within the pedigree. Whole‐exome sequencing revealed a single novel homozygous missense mutation within this locus, in SLC12A1, encoding the Na‐K‐Cl cotransporter, NKCC2, in accordance with the clinical diagnosis. In this concise study, we report a novel missense mutation within the SLC12A1 gene, causing a severe form of ABS type I, the first to be described in Israeli Bedouins, with unusual clinical features of hypernatremia caused by nephrogenic diabetes insipidus and putatively related micrognathia with upper airway abnormalities .